No barrier breakdown between human and cattle schistosome species in the Senegal River Basin in the face of hybridisation. Issue 13 (December 2019) - Boon, Nele A.M.; Mbow, Moustapha; Paredis, Linda; Moris, Pieter; Sy, Ibrahima; Maes, Tim; Webster, Bonnie L.; Sacko, Moussa; Volckaert, Filip A.M.; Polman, Katja; Huyse, Tine
Graphical abstract: Highlights: A strong reproductive boundary between Schistosoma haematobium and Schistosoma bovis persists in co-endemic settings . Schistosoma haematobium populations were spatially differentiated in the Senegal River Basin. Genetic differentiation of S. haematobium appeared to not be associated with S. bovis introgression. Abstract: Schistosomiasis is widely distributed along the Senegal River Basin (SRB), affecting both the human population and their livestock. Damming of the Senegal River for irrigation purposes in the 1980s induced ecological changes that resulted in a large outbreak of Schistosoma mansoni, followed a few years later by an increase and spread of Schistosoma haematobium infections. The presence of hybrid crosses between the human and cattle schistosomes, S. haematobium and Schistosoma bovis, respectively, is adding complexity to the disease epidemiology in this area, and questions the strength of the species boundary between these two species . This study aimed to investigate the epidemiology of S. haematobium, S. bovis and their hybrids along the Senegal River basin using both microsatellite genetic markers and analysis of mitochondrial and nuclear DNA markers. Human schistosome populations with a S. haematobium cox1 mtDNA profile and those with a S. bovis cox1 mtDNA profile (the so-called hybrids) appear to belong to a single randomly mating population, strongly differentiated from the pure S. bovis found in cattle. These results suggest that, in northern Senegal, a strong species boundary persists between human and cattle schistosome species and there is no prolific admixing of the populations. In addition, we found that in the SRB S. haematobium was spatially more differentiated in comparison to S. mansoni. This may be related either to the presence and susceptibility of the intermediate snail hosts, or to the colonisation history of the parasite.